LINEAR AND NON-LINEAR RELATIONSHIP OF CAPITAL STRUCTURE TO FIRM PERFORMANCE WITH AGENCY COST AS MEDIATING AND MODERATING VARIABLE - Tjen, Michele; Imelda, Elsa (Graduate Program of Universitas Tarumanagara, 2025)
This study was conducted examine both linear and non linear impact of capital structure to firm performance with agency cost as both moderating and mediating variable in capital structure and firm performance relationship in non-cyclical business in Indonesia that registered to Indonesia Stock Exchange for a period on 2021-2023. Purposive sampling is done to gain sample in this research, which result to a total of 54 non-cyclical companies. This study uses STATA 17 as a statistic tools to help in analyzing the multiple regression method. MEDSEM in STATA 17 is also used to analyse the mediation effect in this study. In this study, firm performance is calculated using return on equity (ROE). The capital structure counted using leverage, and agency cost is calculated with a measurement of asset utilization ratio (AUR). The result shows that capital structure has a significant negative relationship effect on firm performance, while agency cost shows a significant positive relationship to firm performance. Capital structure resulted to a significant non-linear effect on firm performance. Capital structure doesn't not have a significant effect on firm performance when using agency cost as moderation. Agency cost doesn’t mediate capital structure to effect firm performance. So,the management center it’s attention on the achieving optimal capital structure and control the agency cost in order to increase the firm performance.